Histopathological evaluation of skin wound healing in rabbits treated by systemic dexamethasone - Kashmola, Muhanad Ali Hamdon; Al-Ani, Imad Matloub Dally; Mustafa, Nazih Shaban; Mustafa Al-Ahmad, Basma Ezzat (Department of Anatomy, National University of Singapore, 2012)
The present study was designed to evalurate the effect of dexamethasone on skin wound healing. Fifteen albino rabbits of 6.5 months age were used; an incision and suture was performed on the back skin of ten experimental rabbits previously treated with daily intramuscular injection of 2ml ampoule containing 4 mg dexamethasone for one month and on fi ve control rabbits received 2ml normal saline for the same period. Biopsies of operated skin after 10 days of incision were processed for histopathological evaluation. Histological examination showed delay healing in experimental group in comparison to control group. It is concluded that prolonged use of dexamethasone or misuse of this drug suppress wound healing.